Clinical outcomes in breast angiosarcoma patients: A rare tumor with unique challenges. Issue 8 (4th December 2017) - Gervais, Mai‐Kim; Burtenshaw, Sally M.; Maxwell, Jessica; Dickson, Brendan c.; Catton, Charles N.; Blackstein, Martin; McCready, David; Escallon, Jaime; Gladdy, Rebecca A.
Abstract : Background: Breast angiosarcoma (AS) accounts for less than 1% of all breast cancers. The goal of this study was to determine patient outcomes in radiation‐associated angiosarcoma of the breast (RAAS) and sporadic AS. We evaluated patterns of recurrence and predictors of breast AS survival. Methods: Patients with pathologically confirmed AS from 1994 to 2014 referred to Mount Sinai Hospital/Princess Margaret Cancer Centre were included. Primary outcome was overall survival (OS). Secondary outcomes were disease‐free survival (DFS), clinicopathologic characteristics, patterns of recurrence and factors predictive of survival. Kaplan‐Meier and log‐rank tests were used for OS and DFS. Results: Twenty‐six patients were included: 6 with sporadic AS and 20 with RAAS. Median follow‐up was 24 months. Five‐year OS for RAAS and sporadic subgroups were 44% and 40%, respectively ( P  = ns). Five‐year DFS for RAAS and sporadic subgroups were 23% and 20%, respectively ( P  = ns). Overall recurrence rate was 67% with median time to recurrence of 11 months. Age, tumor depth, margin status, and tumor size were not statistically significant predictive factors for OS and DFS. Discussion: Breast AS is associated with poor survival and high recurrence rates. Prognosis may be mainly determined by its aggressive biology. Referral to tertiary care centers for multimodality treatment is recommended.